A RARE CASE OF DYSTOCIA DUE TO FOETAL ANASARCA AND ITS MANAGEMENT IN A PERSIAN QUEEN CAT - J. Umamageswari; Dhanasekara Varma; K. Ravikumar; R. Sureshkumar; U.S. Kalyan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A 9-month-old female Persian cat was presented with a history of vaginal discharge and straining. On clinical examination, serosanguinous discharge was noticed in the vaginal region. Radiographic and ultrasonographic examination revealed the presence of one dead foetus, which was removed surgically. Gross examination, radiographic and CT imaging of the dead male anasarca foetus revealed an abnormal accumulation of fluid in the subcutaneous tissues.